2014
DOI: 10.2967/jnumed.114.144881
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Very Late Antigen-4 in Melanoma: Comparison of68Ga- and64Cu-Labeled NODAGA and CB-TE1A1P-LLP2A Conjugates

Abstract: Melanoma is a malignant tumor derived from epidermal melanocytes, and it is known for its aggressiveness, therapeutic resistance, and predisposition for late metastasis. Very late antigen-4 (VLA-4; also called integrin α4β1) is a transmembrane noncovalent heterodimer overexpressed in melanoma tumors that plays an important role in tumor growth, angiogenesis, and metastasis by promoting adhesion and migration of cancer cells. In this study, we evaluated 2 conjugates of a high-affinity VLA-4 peptidomimetic ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 23 publications
6
68
0
Order By: Relevance
“…CB-TE1A1P-PEG 4 -LLP2A was synthesized and radiolabeled as described previously (13). The supplemental data provide details (supplemental materials are available at http://jnm.snmjournals.org).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CB-TE1A1P-PEG 4 -LLP2A was synthesized and radiolabeled as described previously (13). The supplemental data provide details (supplemental materials are available at http://jnm.snmjournals.org).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated the proof-of-principle molecular imaging of VLA-4 in murine 5TGM1 myeloma subcutaneous tumors using the PET radiopharmaceutical 64 Cu-(CB-TE1A1P)-LLP2A (12). Recently Beaino et al demonstrated imaging of VLA-4–positive melanoma mouse models using 64 Cu-CB-TE1A1P-PEG 4 -LLP2A ( 64 Cu-LLP2A) (13). 64 Cu-LLP2A possesses ideal pharmacokinetic features such as optimal bioavailability (by virtue of added PEG chains), enhanced solubility, and high 64 Cu specific activity (~37 MBq/μg).…”
mentioning
confidence: 99%
“…Fasted mice were imaged on an Inveon Small Animal Multimodal PET/CT scanner 1 hour following intravenous (lateral tail vein) administration of 7.4 ± 0.74 MBq (200 ± 20 µCi; 100 µL) [ 18 F]-2-fluorodeoxyglucose (FDG; IBA Pharmaceuticals, Dulles, VA) and analyzed as described previously [24]. …”
Section: Methodsmentioning
confidence: 99%
“…11,12 Harsh labeling conditions such as high temperature and long labeling time were usually required for CB-TE2A chelators to get decent labeling yields, limiting their applications in labeling temperature-sensitive biomolecules such as antibodies, although the phosphonate-based cross-bridged chelators such as CB-TE1A1P can be labeled at lower temperatures and have demonstrated success in both antibody and peptide labeling. 1316 There remains a need for a diverse array of BFCs, particularly those that can be readily synthesized, labeled with radiometals at low temperatures and show specficity for a particular radiometal. Derivatives of the polyaminocarboxylate NOTA were revisited, because of their convenient radiolabeling of 64 Cu and good in vivo stability.…”
Section: Introductionmentioning
confidence: 99%